Hygiene knowledge and practices and determinants of occupational safety among waste and sanitation workers in Bangladesh during the COVID-19 pandemic - Mahbub-Ul Alam; Fazle Sharior; Dewan Muhammad Shoaib; Mehedi Hasan; Kazy Farhat Tabassum; Sharika Ferdous; Moushumi Hasan; Mahbubur Rahman; James B. Tidwell; Mariam Zaqout; Makfie Farah; Md. Azizur Rahman; et al. (Elsevier, 2022)
Waste and sanitation workers provide essential services to society. In most low-and middle-income countries, they are often mistreated and lack access to necessary personal protective equipment (PPE) and hygiene facilities that ensure occupational safety in workplaces. COVID-19 has also imposed serious health risks upon these worker groups. This study explores factors associated with poor occupational health and safety based on a conceptual framework. We conducted 499 surveys with five categories of waste and sanitation workers across ten cities in Bangladesh. We performed descriptive analysis and used Firth's logistic regression model following the conceptual framework. The analysis revealed consistent distinctions between workers considered to be in "safe" versus "unsafe" working conditions. The result showed that workers had not been adequately trained, not provided with proper equipment, and many had an informal status that prevented access to hygiene facilities. The workers who received occupational training, knew how to prevent COVID-19 by wearing a face mask, hand washing, and maintaining social distance, maintained protective measures, and practiced proper disposing of PPEs were more likely to be in safe condition. Initiatives to improve the situation of the waste workers who work in unsafe work conditions are still inadequate. Therefore, we recommend supplying proper protective equipment, ensuring a regular supply of gender-specific PPEs, and providing functional facilities necessary to practice personal hygiene and occupational safety, such as handwashing stations, changing rooms, and disposal facilities of used PPEs at the workplace. We also urge increased institutional management procedures, infrastructure that facilitates hygiene practices, and social policies to reduce occupational hazards for the waste workers in Bangladesh during and beyond the COVID-19 pandemic.